2018
DOI: 10.1149/2.0081808jes
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticles-Thiol-Functionalized Reduced Graphene Oxide Coated Electrochemical Sensor System for Selective Detection of Mercury Ion

Abstract: Reduced graphene oxide (rGO) dispersion was obtained by ultrasonication of rGO powder using dodecanethiol (-SH) as an exfoliating agent. Using thiol chemistry, the gold nanoparticles (Au-NPs) were assembled onto the rGO-SH modified glassy carbon electrode (GCE) which showed a strong binding with the surface of the coated electrode. Furthermore, the GCE/rGO-SH/Au-NPs electrode was used to detect mercury (Hg 2+ ) ions in the aqueous solution. When employed as a working electrode, Hg 2+ ions get adsorbed on the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(33 citation statements)
references
References 39 publications
3
30
0
Order By: Relevance
“…GO QDs are interacted strongly with PANI/Ag (AMPSA) NC via electrostatic interaction. Moreover, there are several studies reported the interaction mechanisms of graphene or GO within the hydride materials 14 17 .…”
Section: Introductionmentioning
confidence: 99%
“…GO QDs are interacted strongly with PANI/Ag (AMPSA) NC via electrostatic interaction. Moreover, there are several studies reported the interaction mechanisms of graphene or GO within the hydride materials 14 17 .…”
Section: Introductionmentioning
confidence: 99%
“…The -CH stretching peaks in the region between 2850-3000 cm À1 also confirm the presence of long alkyl tails of thiols on the surface of Ru/rGO as they are absent in the non-modified sample. [24] These À CH peaks are more prominent in C18 molecules as compared to C6 and C12 owing to the long alkyl tail (Supporting Information, Figure S5c). Raman spectroscopy (Supporting Information, Figure S5d) reveals an increase in the I D /I G ratio after the transformation of graphite oxide (GO) to rGO in the solvothermal process.…”
mentioning
confidence: 99%
“…The relative changes of fluorescence intensity from the initial intensity (F 0 /F) at 380 nm, with Hg 2+ at 0–70 µM, are shown Figure 7b. Depending on the concentration of Hg 2+ , the fluorescence intensity is gradually quenched and the detection limit is achieved up to 1.3 nM, which is much better than the other methods listed in Table 1 [50,51,52,53,54,55]. This is due to the presence of -SH and amine groups on the GCNDs surface that can react strongly with Hg 2+ ions.…”
Section: Resultsmentioning
confidence: 96%